PERKEMBANGAN KONSUMSI SKINCARE PADA WANITA - Ananda Fadiyah Arsya, Ananda Fadiyah Arsya; Juliag, Adila Rachma; Sakdiyah, Sabrina Halimatus; Wahyu Purwida, Endryana Putri (Journal of Beauty and Cosmetology (JBC), 2024)
Consumer education is very important for a consumer in carrying out daily activities. This knowledge can provide provisions for someone to be clever in choosing the goods they need and according to the amount of funds they have spent. As a beauty professional, consumer education is important because you use products not only for yourself but also as ingredients when providing services to clients. Skincare is a product that is increasingly developing nowadays, every day the existing trends will continue to change so smart consumers are needed to be able to consume these products. The method used in this research is a qualitative method, namely using data collected from respondents who answered the questionnaire given. This research aims to provide material and an overview of the importance of consumer education in the beauty sector, because many people still do not have knowledge and have experienced bad incidents. With the data and material discussed, it is hoped that it can provide provisions for them and reduce the number of crimes in doing business. in the field of beauty. Keywords: consumers, skincare, women